Biology, classification, and entomopathogen-based management and their mode of action on Tuta absoluta (Meyrick) in Asia - Vivekanandhan, Perumal; Swathy, Kannan; Sarayut, Pittarate; Patcharin, Krutmuang (Frontiers in Microbiology, 2024)
Tuta absoluta, known as the South American tomato leaf miner, significantly impacts tomato plants (Solanum lycopersicum) economically on a global scale. This pest, belonging to the Gelechiidae family, is native to South America and was first identified in Peru in 1917. Since its discovery, T. absoluta has rapidly spread to Europe, Africa, and Asia, severely threatening tomato production in these regions. The widespread application of chemical pesticides against this pest has resulted in significant environmental harm, including contamination of soil and water, and has had negative effects on non-target species such as beneficial insects, birds, and aquatic life. Although substantial research has been conducted, biological control methods for T. absoluta remain insufficient, necessitating further study. This review covers the Biology, Classification, and Entomopathogen-Based Management of T. absoluta (Meyrick) in Asia. It provides essential insights into the pest's life cycle, ecological impacts, and the potential of entomopathogens as biocontrol agents. The detailed information presented aims to facilitate the development of sustainable pest control strategies, minimizing environmental impact and promoting the use of entomopathogens as viable alternatives to chemical pesticides in controlling T. absoluta insect pest.